2002
DOI: 10.1149/1.1486454
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Actuators with Intrinsic Stress Gradient

Abstract: Electrostatic actuators based on microelectromechanical systems ͑MEMS͒ have many attractive features for use as variable capacitors in high-frequency applications. The devices consist of two electrodes, one fixed and the other movable. In this study, a curved, cantilever beam was used as the movable electrode. A novel process has been developed for fabricating an all-gold, curved beam. The cantilever beams were curved due to an intrinsic stress gradient in the metal. Electroplating and conventional lithography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…14 It was observed that as the length of the beam increases, the second-order polynomial description of the beam curvature becomes less accurate and deviations from the stress gradient model become more severe. 14 The movable electrodes with large intrinsic stress gradients created by the deposition of 0.2 and 0.3 m of hard gold have shown an initial curvature of polynomial order greater than 2. The hard gold thickness variation along the length of the movable electrode during electroplating would result in nonuniform stress gradient along the length leading to the curved beam with higher order curvature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 It was observed that as the length of the beam increases, the second-order polynomial description of the beam curvature becomes less accurate and deviations from the stress gradient model become more severe. 14 The movable electrodes with large intrinsic stress gradients created by the deposition of 0.2 and 0.3 m of hard gold have shown an initial curvature of polynomial order greater than 2. The hard gold thickness variation along the length of the movable electrode during electroplating would result in nonuniform stress gradient along the length leading to the curved beam with higher order curvature.…”
Section: Discussionmentioning
confidence: 99%
“…A model for calculating the deflection of the beam after release due to relief of the residual stress was presented in Part I of this study. 14 The initial curvature of the cantilever beam with a built-in stress gradient can also be modeled by assuming the beam to be made of two different materials. 13 An internal stress gradient can be created by using two materials with dissimilar coefficient of thermal expansion ͑CTE͒.…”
Section: Theorymentioning
confidence: 99%
“…The total intrinsic stress in the beam can be divided into a constant mean stress σ 0 and a gradient stress σ 1 . Assuming a linear stress profile within the beam, σ 0 and σ 1 can be expressed as [12,13]…”
Section: Analysis Of the Intrinsic Stressmentioning
confidence: 99%
“…The assumption of linear stress distribution, i.e. constant stress gradient, is frequently employed in the literature [10,14,[16][17][18], which is especially proper for very thin films such as the 1-lm-thick nickel film of this study:…”
Section: Residual Stress Gradients and Their Characterizationmentioning
confidence: 99%